Análisis tafonómico de moluscos holocenos en el área costera del Estuario de Bahía Blanca, Argentina - SPAGNUOLO, JORGE; FARINATI, ESTER; ALIOTTA, SALVADOR (Pesquisas em Geociências, 2001)
At the south west of the Buenos Aires province, Argentina, on the northern coast of the Bahía Blanca Estuary, sand-shell ridges sub-parallel to the coastline generated during the Holocene transgression-regression were deposited. These structures are composed mostly of coarse to medium sand and a high proportion of molluscs shells (19 species of bivalves and 16 species of gastropods). For this study three taxa from the fossil association located in the ridges (Brachidontes rodriguezi, Tegula patagonica and Crepidula aculeata) were selected and the mechanisms of taphonomic alteration that affected them were qualified. By means of ternary taphograms the variation of five taphonomic attributes (bioerosion, encrustation. fragmentation. wear and dissolution) was established. It has been determined that the bioestratinomic processes are subordinated to the fossildiagenetic mechanisms, where dissolution has left a series of taphonomic signatures. Based upon the taphonomic attributes of the fossil association a high stand sea level cycle with an important contribution of storm waves that affected the biogenic production area were established as a representation of the paleoenvironmental evolution.